(untitled) (Journal of Hama University, 2022)
The aim of this research is to determine the role of social responsibility with its dimensions (economic, legal, moral, charitable, environmental) in achieving sustainable development, in the following industrial companies under study: Food Industries Development Company (KATAKIT) in Damascus, Sabbagh & Partners Company for Food Industries in Damascus, and Al-Rabie Company for Food Industries in Damascus. The researcher distributed (100) questionnaires to an accessible sample of individuals working in the companies under study and from all administrative levels (highest, middle, and lowest), (90) questionnaires were retrieved, and (8) questionnaires were excluded from them for not completing their data, thus the number of questionnaires That was uploaded (82) questionnaire. The researcher analyzed the data using the statistical analysis program (SPSS 25). At the end of this research, the two researchers reached a set of conclusions, the most important of which are: There is a significant impact of the dimensions of social responsibility (economic, legal, moral, charitable, environmental) in achieving sustainable development in the industrial companies under study. The researchers also made a number of recommendations, including: Taking into account industrial companies in their orientation to perform social responsibility to focus on areas of sustainable development that achieve added value and are beneficial to all segments of society and stakeholders.